PROFILE OF STUDENT’S CONCEPT UNDERSTANDING IN COMPARATIVE MATERIAL WITH VALUE AND VARIOUS GRADES IN CLASS VII - Widhiani, Ni Luh Regita Eka; ini, Anggra; Sugita, Gandung; Hajar, Ibnu (JME (Journal of Mathematics Education), 2023)
This study aims to obtain a description or description of students' understanding of the concept of value comparison material and value turning at SMP Negeri 1 Ampibabo. The results of this study indicate that (1) subjects with high mathematical ability: are able to restate the concept of comparison of values and values in their own language or words; able to identify comparisons of value and return of value based on the definition of comparison of value and return of value; able to provide examples and non-examples of comparisons of value and return of value according to the characteristics of comparison of value and return of value; and able to use, utilize and choose the right procedure to solve the problem of comparison of value and return of value with complete and correct completion steps (2) subjects with moderate mathematical abilities are able to restate the concept of comparison of value and return of value by using their own sentences; able to identify comparisons of value and return of value based on the definition; able to provide examples and non-examples of comparisons of value and return of value according to the characteristics of comparison of value and return of value; and are able to use the concept of equivalent comparisons to solve comparison problems of equal value but are less able to understand the problem of comparison of value reversed so that they are wrong in completing answers and are less thorough in calculations (3) subjects with low mathematical abilities are able to restate the concept of comparison of value and reverse value in their own language ; able to identify comparisons of value and return of value based on the definition of comparison of value and return of value; able to provide examples and non-examples of comparisons of value and return of value according to the characteristics; but unable to use, utilize and choose the right procedure in solving the problem of comparison of value and return on value.